The effect of corporate social responsibility dimensions on consumer satisfaction and perceived value: the case of the automobile sector in Portugal - Loureiro, S. M. C.; Sardinha, I.; Reijnders, L. (Journal of Cleaner Production, 2012)
Previous research has suggested that a good record of corporate social responsibility (CSR) or corporate social performance (CSP) positively influences corporate financial performance (CFP) by lowering costs and increasing productivity. Corporate financial performance might also be impacted by the effect of perceived CSR on consumer satisfaction. In this study, we present research on the contribution to consumer satisfaction of the perceived CSR of three car manufacturers in terms of labor practices, community development and environmental performance within a group of 329 Portuguese car buyers and users. These consumers valued environmental performance much more than activities related to labor practices and community development. However, determinants outside the realm of CSR, such as perceived product and service quality and empathy with the brand, were much more important for Portuguese consumers than CSR. The overall importance of CSR for consumer satisfaction suggests that in the automobile industry, CSR may not only contribute to better financial performance by directly reducing costs and increasing productivity but may also contribute indirectly by increasing consumer satisfaction.